CHA2DS2-VASc and CHADS2 scores for risk stratification of major adverse cardiovascular events in the COMPASS trial. (25th November 2020) - Sen, J; Tonkin, A; Varigos, J; Fonguh, S; Berkowitz, S.D; Yusuf, S; Verhamme, P; Vanassche, T; Anand, S; Fox, K.A.A; Eikelboom, J.W; Amerena, J
Abstract: Background: The COMPASS (Cardiovascular Outcomes for People Using Anticoagulation Strategies) trial demonstrated that the combination therapy of rivaroxaban and aspirin reduced major adverse cardiovascular events (MACE) compared to aspirin alone in patients with chronic coronary artery disease (CAD) and/or peripheral artery disease (PAD). Purpose: We assessed whether the CHA2DS2-VASc (congestive heart failure (CHF), hypertension, age ≥75 years, diabetes, stroke/transient ischemic attack (TIA)/thromboembolism, vascular disease, age 65–75 years, and sex category) and CHADS2 (CHF, hypertension, age ≥75 years, diabetes, stroke/TIA) scores used to predict the risk of stroke in patients with atrial fibrillation, can be used identify vascular patients at highest risk of recurrent events who may derive greatest benefits of treatment. Methods: In COMPASS patients, the predictive accuracy of CHA2DS2-VASc and CHADS2 scores were assessed for MACE, bleeding and net clinical benefit using Cox proportional hazards model. Kaplan-Meier estimates of cumulative risk and absolute risk differences were used to examine the effects of rivaroxaban plus aspirin compared with aspirin alone over 30 months according to risk score categories. Results: In 27, 395 participants with CAD and/or PAD, a high CHA2DS2-VASc score (6–9) was associated with 3 times greater absolute risk of MACE compared to a low score (1–2) (hazard ratio=3.39, 95% CI: 2.54–4.51, p<0.0001). The effects of combination therapy with rivaroxaban and aspirin on MACE, bleeding and net clinical benefit were consistent across CHA2DS2-VASc and CHADS2 score categories, with the greatest benefit in those with the highest risk scores (Figure 1). The greatest reduction in MACE with rivaroxaban and aspirin compared to aspirin only was observed in patients treated for 30 months with highest CHA2DS2-VASc score (6–9) (23 events per 1000 patients prevented) or highest CHADS2 score (3–6) (25 events per 1000 patients prevented). There was increased bleeding in patients with higher CHA2DS2-VASc and CHADS2 scores, but net clinical benefit was preserved across all risk categories and was greatest in those with the highest risk scores. Conclusion: The CHA2DS2-VASc or CHADS2 scores can be used in patients with chronic CAD and/or PAD to identify patients who are at highest risk of MACE, and therefore likely to achieve the greatest benefit of dual pathway inhibition with the combination of rivaroxaban and aspirin compared with aspirin alone. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): This study was sponsored by Bayer AG.